BLOOD BIOCHEMICAL ANALYSIS: ASSESSING THE CHEMICAL STATE OF THE BODY (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Blood biochemical analysis is one of the primary laboratory tests widely used in medicine, aimed at determining the levels of various substances, enzymes, ions, hormones, and metabolites in the human body. Through this analysis, doctors assess the overall health of the patient, the state of metabolism, as well as the functioning of the liver, kidneys, heart, endocrine system, and other organs. Blood biochemical analysis plays an important role in diagnostics, treatment planning, and preventive examinations.